Bacterial diversity among the fruit bodies of ectomycorrhizal and saprophytic fungi and their corresponding hyphosphere soils - Yaping Liu (Nature Portfolio, 2018)
Abstract Macro-fungi play important roles in the soil elemental cycle in terrestrial ecosystems. Many researchers have focused on the interactions between mycorrhizal fungi and host plants, whilst comparatively few studies aim to characterise the relationships between macro-fungi and bacteria in situ. In this study, we detected endophytic bacteria within fruit bodies of ectomycorrhizal and saprophytic fungi (SAF) using high-throughput sequencing technology, as well as bacterial diversity in the corresponding hyphosphere soils below the fruit bodies. Bacteria such as Helicobacter, Escherichia-Shigella, and Bacillus were found to dominate within fruit bodies, indicating that they were crucial in the development of macro-fungi. The bacterial richness in the hyphosphere soils of ectomycorrhizal fungi (EcMF) was higher than that of SAF and significant difference in the composition of bacterial communities was observed. There were more Verrucomicrobia and Bacteroides in the hyphosphere soils of EcMF, and comparatively more Actinobacteria and Chloroflexi in the hyphosphere of SAF. The results indicated that the two types of macro-fungi can enrich, and shape the bacteria compatible with their respective ecological functions. This study will be beneficial to the further understanding of interactions between macro-fungi and relevant bacteria.